Pathway to encapsulate the surface water quality model and its applications as cloud computing services and integration with EDSS for managing urban water environments. (February 2022) - Jiang, Jiping; Pang, Tianrui; Zhang, Fengyuan; Men, Yunlei; Yadav, Harsh; Zheng, Yi; Chen, Min; Xu, Hongliang; Zheng, Tong; Wang, Peng
Abstract: The encapsulation of specific management measurements and computing services is rarely reported for surface water EDSS. To promote the efficiency and reduce the complexity of surface water EDSS development, a generic pathway to encapsulate the surface water quality model and its applications as cloud computing services is proposed. The web service is implemented under the OpenGMS framework. Two typical management measurements, water assimilative capacity allocation and pollution load reduction planning are encapsulated based on the advanced version of the WASP program. An EDSS instance of the Maozhou River, Shenzhen, is developed, which provides precise management measurements for COD and NH3 –N control. Management services provided by other models, EFDC and SWMM, are also implemented under this novel framework. The proposed pathway provides the merits of rapid development, easy deployment, and maintenance of an advanced EDSS. It presents a good demonstration of coupling advanced WASP programs within EDSS for receiving water management. Highlights: Pathway: model control – application component–service encapsulate–DSS integration. Surface water quality management measurements first encapsulated as web services. Latest WASP model and its applications are implemented as services by OpenGMS. Assimilation capacity computation and load reduction planning integrated in an EDSS. A preliminary industrial cloud for surface water quality management was formed.